Identity and identity crisis in adolescence - Vaičiulienė, Aldona (Psichologija, 1999)
The purpose in a study of 263 secondary school students at age 16-17 was to assess the level of identity development in the middle adolescence. Methods used were an identity status questioning (EOMEIS-2) and Shostrom's Personal Orientation Inventory (POI). In comparison with ideological sphere, interpersonal sphere occurred as more achieved in identity development. The results show statistically meaningful differences in identity development level between two spheres. Interpersonal sphere in a high degree is distinguished by adolescent crisis as period of explorations. The correlation of identity achievement statuses with POI scales scores suggests that, identity achievement is related to the personal need to be inner-directed and self-actualizing.
Keywords: identity; adolescence